Pragmatics Study on Deixis Analysis in Expository Text by Students EFL Secondary School - Shalahudin Ayyub; Peptia Asrining Tyas (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study attempts to identify the varieties of deixis (according to Levinson's deixis theory) employed and the major deixis types used by EFL secondary school students in expository texts. This study used qualitative research as a method and used a documentary technique for the analysis. The analysis's conclusion demonstrates that Students in EFL secondary schools use every sort of deixis in writing expository text. The deixis that is mostly used is discourse deixis, which is 158 times, the second is followed by person deixis with 150 times, time deixis with 14 times, place deixis with 10 times, and the lowest is social deixis which is only 6 times. According to the findings of this study, discourse deixis becomes the predominant type used in the expository texts. This result implies that the dominant deixis employed varies depending on the type of text.